Model study of effect of M = Li+, Na+, Be2+, Mg2+, and Al3+ ion decoration on hydrogen adsorption of metal-organic framework-5 - Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2010)
The effect of light metal ion decoration of the organic linker in metal organic framework MOF 5 on its hydrogen adsorption with respect to its hydrogen binding energy (Delta B E) and gravimetric storage capacity is examined theoretically by employing models of the form MC6H6 nH(2) where M = Li+ Na+ Be2+ Mg2+ and Al3+ A systematic investigation of the suitability of DFT functionals for studying such systems is also carried out Our results show that the interaction energy (Delta E) of the metal ion M with the benzene ring Delta B E and charge transfer (Q(trans)) from the metal to benzene ring exhibit the same increasing order Na+ < Li+ < Mg2+ < Be2+ < Al3+ Organic hnker decoration with the above metal ions strengthened H-2 MOF 5 interactions relative to its pure state However amongst these ions only Mg2+ ion resulted in Delta B E magnitudes that were optimal for allowing room temperature hydrogen storage applications of MOF 5 A much higher gravimetric storage capacity (6 15 wt % H-2) is also predicted for Mg2+ decorated MOF 5 as compared to both pure MOF 5 and Li+ decorated MOF (C) 2010 Professor T Nejat Veziroglu Published by Elsevier Ltd All rights reserved
Keywords: Binding energy; Hydrogen adsorption; Hydrogen storage; Metal organic frameworks

Ab initio and periodic DFT investigation of hydrogen storage on light metal-decorated MOF-5 - Dixit, Mudit; Maark, Tuhina Adit; Pal, Sourav (International Journal of Hydrogen Energy, 2011)
The effect of light metal (M = Li, Be, Mg, and Al) decoration on the stability of metal organic framework MOF-5 and its hydrogen adsorption is investigated by ab initio and periodic density functional theory (DFT) calculations by employing models of the form BDC:M-2:nH(2) and MOF-5:M-2:nH(2), where BDC stands for the benzenedicarboxylate organic linker and MOF-5 represents the primitive unit cell. The suitability of the periodic DFT method employing the GGA-PBE functional is tested against MP2/6-311 + G* and MP2/cc-pVTZ molecular calculations. A correlation between the charge transfer and interaction energies is revealed. The metal-MOF-5 interactions are analyzed using the frontier molecular orbital approach. Difference charge density plots show that H-2 molecules get polarized due to the charge generated on the metal atom adsorbed over the BDC linker, resulting in electrostatic guest-host interactions. Our solid state results show that amongst the four metal atoms, Mg and Be decoration does not stabilize the MOF-5 to any significant extent. Li and Al decoration strengthened the H-2-MOE-5 interactions relative to the pure MOF-5 exhibited by the enhanced binding energies. The hydrogen binding energies for the Li- and Al-decorated MOF-5 were found to be sensible for allowing reversible hydrogen storage at ambient temperatures. A high hydrogen uptake of 4.3 wt.% and 3.9 wt.% is also predicted for the Li- and Al-decorated MOF-5, respectively. Copyright (C) 2011, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: ab initio calculations; Density functional theory; Hydrogen binding energies; Hydrogen storage; Metal-Pi-Arene interactions

Scandium-decorated MOF-5 as potential candidates for room-temperature hydrogen storage: a solution for the clustering problem in MOFs - Dixit, Mudit; Maark, Tuhina Adit; Ghatak, Kamalika; Ahuja, Rajiv; Pal, Sourav (Journal of Physical Chemistry C, 2012)
Transition-metal-based systems show promising binding energy for hydrogen storage but suffer from clustering problem. The effect of light transition metal (M = Sc, Ti) decoration, boron substitution on the hydrogen storage properties of MOF-5, and clustering problem of metals has been investigated using ab initio density, functional theory. Our results of solid-tate calculations reveal that whereas Ti clusters strongly Sc atoms do not suffer from this problem when decorating MOF-5. Boron substitution on metal-decorated MOF-5 enhances the interaction energy of both the metals with MOF-5. Sc-decorated MOF-5 shows a hydrogen storage capacity of 5.81 wt % with calculated binding energies of 20-40 kJ/mol, which ensures the room-teniperature applicability of this hydrogen storage material.